Variability in Skin Prick Test Results Performed by Multiple Operators Depends on the Device Used - Rebecca L. Werther, MBBS, FRACP; Sharon Choo, MBBS, FRACP, FRCPA; Katherine J. Lee, BSc, PhD; Debra Poole, BNurs; Katrina J. Allen, MBBS, BMedSc, FRACP, PhD; Mimi L.K. Tang, MBBS, PhD, FRACP, FRCPA (World Allergy Organization Journal, 2012)
Background The variability of skin prick test results when carried out by multiple users has not previously been assessed across different devices or between different sites on the body. Such multiuser variability has important implications for clinical practice.Objectives We assessed the variability of measurements from 4 commonly used single-headed skin test devices when used by multiple operators and examined whether the variability in performance was different on the back compared with the forearm.Methods Eight adult volunteer ''operators'' were trained in the use of 4 devices: Greer Pick, Quintip, Stallergenes Lancet, and Feather Lancet. Each operator performed a histamine skin prick test with all devices on the backs and forearms of 5 volunteer ''receivers.'' Variability in results was assessed using a multilevel (random effects) regression model.Results After controlling for variation between users and receivers, the residual variability or ''measurement error'' was least for the Stallergenes Lancet, closely followed by the Quintip. The Greer Pick had the greatest variability. There was greater variability in measurements on the arm compared with the back.Conclusions The devices using the ''puncture'' method (Stallergenes Lancet, Quintip) provide less variability in results than those using a ''prick'' method when carried out by multiple users (Greer Pick and Feather Lancet). Testing on the back also gives less variable results compared with the arm. Keywords: device, skin prick test, variability